“I DON’T KNOW HOW I WANT TO GO BUT I DO KNOW THAT I WANT TO BE THE ONE WHO DECIDES” – THE RIGHT TO DIE – THE HIGH COURT OF SOUTH AFRICA RULES IN Robert James Stransham-Ford and Minister of Justice and Correctional Services; The Minister of Health Professi - Glynis van der Walt; Emma Kate du Plessis (Obiter, 2015)
The present case concerns the legality of assisted suicide and active euthanasia in South Africa. This particular issue has been a major point of contention, having been debated in South Africa and elsewhere for many years and is generally accepted to be unlawful. In November 1998, the South African Law Commission submitted a report to the then Minister of Health on this issue, entitled “Euthanasia and the Artificial Preservation of Life”. At the time of its submission, the country was facing a number of imposing crises, including the HIV/AIDS epidemic. As a consequence of this, this report did not receive the necessary attention of either the Minister of Health or the legislature at the time. Sixteen years have since passed and in the interim South Africa became a democracy (in 1994). A Constitution was promulgated that inter alia guarantees fundamental human rights to all persons. However, the status quo on euthanasia and assisted suicide has remained unchanged in South Africa.The advances made in medical science have resulted in patients living longer. For some, the advances in medical technology are welcomed in that they can prolong a meaningful life. For others, however, the prolonging of a poor quality of life is viewed as a burden rather than a benefit.On an international level the importance placed on the autonomy of the mentally-sound patient’s right to refuse any medical treatment that will unnecessarily prolong the agony of such patient, and also, for such a patient to receive assistance in ending his or her life at a point where his or her suffering has become so unbearable, has received more attention (at present there are 11 countries or States which recognise the right to assisted suicide and active euthanasia). In South Africa, doctors are placed in a situation where they might wish to act in the best interest of the patient under their care, but at the same time there is no clarity as to their legal position and there is uncertainty as to the scope and content of the legal obligation to provide medical care. The basis for this uncertainty will be referred to within this case note. The potential of being exposed to civil claims and criminal prosecution should they decide to withhold life support to the patient or to provide drugs which may shorten the suffering of the patient, notwithstanding the fact that they are acting in accordance with the wishes of the patient, is real. Cases are dealt with on an ad hoc basis and with no national policy.With the dawning of the constitutional era, a consideration and decision on the right of an individual to assisted suicide in light of the principles of the Bill of Rights contained in the Constitution of South Africa is long overdue. For this reason, the present case is of great significance. The matter concerned an urgent application requiring an immediate decision regarding the Applicant’s request that a medical practitioner, registered in terms of the Health Professions Act 56 of 1974, terminate or enable the Applicant to terminate his life by the administration or provision of a lethal agent which would enable him to end his life. The application was opposed by the Minister of Justice and Correctional Services, the Minister of Health, the Health Professional Council of South Africa and the National Director of Public Prosecutions.